Faktor Yang Mempengaruhi Konsumen Memilih Kolam Renang Muslimah Al-Hikmah Sport Center di Surabaya - Hardianto, Anneke Ratnasari; Ratnasari, Ririn Tri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study is to identify factors that influence consumers on choosing Al-Hikmah Sport Center Muslimah Swimming Pool in Surabaya. It related to increasing ofÂ peopleâs awareness to do physical activities, especially swimming.This study used quantitative research methods with exploratory factor analysis.Characteristics of the respondents in this study is Muslim consumers of Al-Hikmah Sport CenterÂ Muslimah Swimming Pool that have come at least twice in a last month. Sample amount onÂ preliminary test by doing written interview are 20 respondents and the main test need 125Â respondents. Sampling technique that used is non-probability sampling. Sampling was doneÂ using accidental sampling and purposive sampling.The results of the study showed that there are six factors that influence consumers onÂ choosing Al-Hikmah Sport Center Muslimah Swimming Pool in Surabaya. The sixth factors areÂ named by the factor of similarity motives, securities, location, facilities, water qualities, andÂ the experiences.